Modulator effects of interleukin-1beta and tumor necrosis factor-alpha on AMPA-induced excitotoxicity in mouse organotypic hippocampal slice cultures - Bernardino, Liliana (2005)
The inflammatory cytokines interleukin-1\u2424 and tumor necrosis factor-\u2423 (TNF-\u2423) have been identified as mediators of several forms of neurodegeneration in the brain. However, they can produce either deleterious or beneficial effects on neuronal function. We investigated the effects of these cytokines on neuronal death caused by exposure of mouse organotypic hippocampal slice cultures to toxic concen- trations of AMPA. Either potentiation of excitotoxicity or neuroprotection was observed, depending on the concentration of the cytokines and the timing of exposure. A relatively high concentration of mouse recombinant TNF-\u2423 (10 ng/ml) enhanced excitotoxicity when the cultures were simultaneously exposed to AMPA and to this cytokine. Decreasing the concentration of TNF-\u2423 to 1 ng/ml resulted in neuroprotection against AMPA-induced neuronal death independently on the application protocol. By using TNF-\u2423 receptor (TNFR) knock-out mice, we demonstrated that the potentiation of AMPA-induced toxicity by TNF-\u2423 involves TNF receptor-1, whereas the neuroprotective effect is mediated by TNF receptor-2. AMPA exposure was associated with activation and proliferation of microglia as assessed by macrophage antigen-1 and bromodeoxyuridine immunohistochemistry, suggesting a functional recruitment of cytokine- producing cells at sites of neurodegeneration. Together, these findings are relevant for understanding the role of proinflammatory cytokines and microglia activation in acute and chronic excitotoxic conditions